2007
DOI: 10.1186/1471-2334-7-84
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gene targets against dormant phase Mycobacterium tuberculosis infections

Abstract: Background: Mycobacterium tuberculosis, the causative agent of tuberculosis (TB), infects approximately 2 billion people worldwide and is the leading cause of mortality due to infectious disease. Current TB therapy involves a regimen of four antibiotics taken over a six month period. Patient compliance, cost of drugs and increasing incidence of drug resistant M. tuberculosis strains have added urgency to the development of novel TB therapies. Eradication of TB is affected by the ability of the bacterium to sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
145
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(149 citation statements)
references
References 124 publications
(140 reference statements)
2
145
1
1
Order By: Relevance
“…We show that D-Mtb downmodulates expression of the esat6 gene, suggesting that in dormancy M. tuberculosis secretes reduced amounts of ESAT-6 in comparison with R-Mtb. Moreover, expression of the gene Rv3309c, which encodes for SapM, was previously found downregulated in D-Mtb obtained with the same Wayne culture method we used and in stressed mouse macrophages (46). Taken together, these data are highly suggestive for the pivotal role played by the reduced expression of esat6 and SapM as a possible mechanism used by D-Mtb to permit phagosome maturation and downstream events leading to an increased Ag processing and presentation to specific CD4 + T lymphocytes.…”
Section: Discussionsupporting
confidence: 58%
“…We show that D-Mtb downmodulates expression of the esat6 gene, suggesting that in dormancy M. tuberculosis secretes reduced amounts of ESAT-6 in comparison with R-Mtb. Moreover, expression of the gene Rv3309c, which encodes for SapM, was previously found downregulated in D-Mtb obtained with the same Wayne culture method we used and in stressed mouse macrophages (46). Taken together, these data are highly suggestive for the pivotal role played by the reduced expression of esat6 and SapM as a possible mechanism used by D-Mtb to permit phagosome maturation and downstream events leading to an increased Ag processing and presentation to specific CD4 + T lymphocytes.…”
Section: Discussionsupporting
confidence: 58%
“…The host immune response restricts the development of active infection by quarantining M. tuberculosis in granuloma, while the M. tuberculosis bacterium can persist in granulomatous lesions in a non-replicative state, with the ability to resume growth and activate disease [14]. It has been demonstrated that the stress conditions such as nutrient deprivation and oxygen limitation play a role in inducing non-replicacing persistence [15]. Under normal growth conditions, the antitoxin and toxin are coexpressed from a TA operon and form a stable complex.…”
Section: Rv1991c Rv1991amentioning
confidence: 99%
“…The existence of NrdE in the cell wall fraction of MTB was initially reported by Rosenkrands et al, (2000) (55). Quantitative RT-PCR studies by Murphy et al (2007) on nrdEF2 using the Wayne's model have shown a ten-fold decrease in the expression of nrdEF2 when MTB culture was shifted from log phase to NRP1, followed by a two to three-fold increase from there as the cells entered NRP2 (56). The absence of the NrdF2 protein at NRP1 in our study correlates well with the drastic decrease in expression of nrdEF2 observed by them.…”
Section: Validation Of Quantitative Proteomic Data By Qpcr-tomentioning
confidence: 99%